Financial modelling of meat cattle breeding in Kazakhstan based on a business process map - Altaibayeva, Zhanat; Aiguzhinova, Dinara; Shelomentseva, Valentina; Narynbayeva, Aina; Bauer, Maira (International Journal of Innovative Research and Scientific Studies, 2025)
The study aimed to develop a standardized map of business processes as a basis for creating a production program for livestock activities and their financial modeling at enterprises in Northern Kazakhstan. General scientific and empirical research methods were applied, including logical and systematic approaches, generalization, analysis, synthesis, comparison, and calculations for data collection and processing. The specific conditions and practices of raising, fattening, and breeding livestock in Northern Kazakhstan were summarized and incorporated into the development of the business process map. The developed map reflects the components of the livestock system, detailing a sequence of tasks and procedures carried out using input resources. The research results make an original contribution by addressing key scientific and practical issues in livestock organization: the specific features of livestock business processes have been clarified; a standardized business process map has been developed; and a definition of business processes in livestock farming has been provided. The research results can be applied in the planning of production programs, financial modeling of business processes, and assessing their efficiency.